(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2020)
Agriculture is one of the activities of the primary sector that generates benefits for other sectors. The grass is present in the food diet of Ecuadorians. For this reason, there are several production areas dedicated to the cultivation of this product, which is intended to satisfy the country’s internal demand. The investigation was carried out in the town of Juan Bautista Aguirre, which is located in the province of Guayas. The main economic activity of the Juan Bautista Aguirre locality is the sowing of rice. The objective of the article was to diagnose the socioeconomic situation of the farmers of the rice sector and their families. A quantitativeand qualitative research approach was used. This allowed discovering through direct observation and a survey to detect the main shortcomings that affect the living standards of rice producers: insufficiencies in basic services, environmental deterioration of the environment, little support from local authorities, among others. The research proposed an action plan to be taken into account by local and national authorities with a view to improving the socioeconomic conditions of the residents who constitute the practical object of this research.